Disentangling the perceptual underpinnings of autism: evidence from a face aftereffects experiment - Hennig, Julius; Doose, Arne; Breier, Clara Marie; Soutschek, Alexander; Beyer, Nicole; Schweinberger, Stefan; Kamp-Becker, Inge; Poustka, Luise; Albertowski, Katja; Roessner, Veit; Ehrlich, Stefan (Autism research, 2025)
Existing literature has documented diminished norm-based adaptation (aftereffects) across several perceptual domains in autism. However, the exact underlying mechanisms, such as sensory dominance possibly caused by imprecise priors and/or increased sensory precision, remain elusive. The “Bayesian brain” framework offers refined methods to investigate these mechanisms. This study utilized both model-free (frequentist statistics) and model-based (hierarchical Drift Diffusion Modeling) analytical approaches to compare gender face aftereffects in male adolescents with autism (n = 29) to neurotypical controls (n = 39) using a behavioral choice experiment. Contrary to our initial hypotheses, our analyses did not find support for imprecise priors or increased sensory precision within the autistic group. Instead, we observed generally decreased drift rates towards male but not female stimuli in the autistic group. Thus, our findings suggest a lack of own-gender bias in face processing among the autistic participants. These findings align with more recent behavioral and neurophysiological research observing intact priors in individuals with autism, suggesting that other mechanisms may better explain the perceptual challenges in autism. Our study contributes to the ongoing discourse on perceptual processing in autism, emphasizing the necessity for more nuanced analytical approaches in order to unravel the complexity of this condition.
Zuerst veröffentlicht: 16. Dezember 2024
Gesehen am 26.05.2025